KEPEMIMPINAN KEPALA SEKOLAH PADA ORGANISASI SMP NEGERI 24 MAKASSAR - Syamsiarna Nappu (Perspektif Ilmu Pendidikan, 2009)
The leader and his/her leadership is directly influence the organization members’ behavior and determine the success of the organization to attain its objectives. Of the opinion that to be able to survive, develop, and to compete, this article report a case study conducted at Government Junior High School in Makasar. Having analyzed the available data and information, this study concludes that the school principal as the leader of the school has not fully implemented the principles of learning organization. This study also provides a set of recommendations to improve the leadership in the school.